2010
DOI: 10.1139/f10-083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Columbia River plume on the survival of steelhead (Oncorhynchus mykiss) and Chinook salmon (Oncorhynchus tshawytscha): a numerical exploration

Abstract: Are smolt-to-adult return rates (SARs) for wild steelhead (i.e., sea-run rainbow trout, Oncorhynchus mykiss ) and wild Snake River spring–summer Chinook salmon ( Oncorhynchus tshawytscha ) related to changes in the Columbia River plume at the time that juvenile migrants enter the ocean? We used three-dimensional (3D) numerical models of the baroclinic circulation in the Columbia River estuary–plume–shelf system to simulate within-season variation in plume size and location, comparing the results with SARs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…• In a separate but related project, both DB11 and DB14 were used to address the question of whether the intraseasonal variability in smolt-to-adult survival rates (SARs) for steelhead (Oncorhynchis mykiss) and Snake River spring/summer chinook salmon (O. tshawytscha) are related to conditions in the Columbia River plume when the juvenile migrants enter the ocean [6]. Results suggest that steelhead (but not Chinook) salmon benefit from the plume environment at a narrow window of time around their ocean entry.…”
Section: Progress In 2008/2009mentioning
confidence: 99%
See 1 more Smart Citation
“…• In a separate but related project, both DB11 and DB14 were used to address the question of whether the intraseasonal variability in smolt-to-adult survival rates (SARs) for steelhead (Oncorhynchis mykiss) and Snake River spring/summer chinook salmon (O. tshawytscha) are related to conditions in the Columbia River plume when the juvenile migrants enter the ocean [6]. Results suggest that steelhead (but not Chinook) salmon benefit from the plume environment at a narrow window of time around their ocean entry.…”
Section: Progress In 2008/2009mentioning
confidence: 99%
“…SATURN relies on 3D numerical models [2,3] to systematically simulate and understand baroclinic circulation in the Columbia River estuary-plume-shelf system [4][5][6][7] (Fig. 1).…”
mentioning
confidence: 99%
“…32). Existing multi-year simulation databases of circulation produced by SATURN have multiple applications in understanding plume variability [5] and the role of the plume on salmon survival [6].…”
Section: Modeling and Analysis Of Plume Circulation And Its Implicatimentioning
confidence: 99%
“…Yearling Chinook salmon from the Columbia River enter the ocean and quickly migrate north (Peterson et al 2010). Although general migration patterns are known (Weitkamp 2010, Tucker et al 2011) and environmental correlates have been proposed (Bi et al 2007, Burla et al 2010a, Peterson et al 2010), a comprehensive understanding of the early ocean ecology and migration behavior of these juvenile salmon is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Burke et al (2013) found that the response to (unspecified) large-scale variables, such as the sun or Earth's magnetic field, was stronger than the response to local environmental cues, which suggests that salmon primarily use navigation in their migrations. However, orientation to local conditions is also suggested by the high correlation between yearling Chinook salmon catches and local environmental conditions (Bi et al 2007, Burla et al 2010a, Yu et al 2012.…”
Section: Introductionmentioning
confidence: 99%